Strategic Customers in a Transportation Station: When Is It Optimal to Wait? - Manou, A.; Economou, A.; Karaesmen, F. (Operations Research, 2014)
We consider a transportation station, where customers arrive according to a Poisson process. A transportation facility visits the station according to a renewal process and serves at each visit a random number of customers according to its capacity. We assume that the arriving customers decide whether to join the station or balk, based on a natural reward-cost structure. We study the strategic behavior of the customers and determine their symmetric Nash equilibrium strategies under two levels of information.